Fishermen’s resilience-based management policy on small islands - Hafsaridewi Rani; Sutrisno Dewayany; Koeshendrajana Sonny; Kurniawan Tikkyrino (BIO Web of Conferences)
Community resilience and resource management are closely related, particularly when it comes to preserving social, economic, and environmental well-being in small islands. Policies and regulations that promote sustainable resource management also contribute to the development of more resilient communities. Identifying the indicators also rely on the context of the resilience measured. The purpose of this study is to measuring Fishermen's Resilience in a Policy Framework. Resilience was calculated by comparing scores obtained with maximum scores of resilience index. For data collection, survey method was conducted in Karimunjawa Islands, Central Java Province, Indonesia. The five dimensions of resilience used are social, economic, institutional, infrastructure, and resource. The results presented two categories of resilience namely sufficiently resilient and resilient. Fishers in the category of resilient are fishers in Karimunjawa, Kemujan, and Parang. Fishers in Nyamuk Island are in the category of sufficiently resilient. To enhance the resilience of small-scale fishermen on small islands, the following strategies are recommended: diversify livelihoods, strengthen social protection systems, optimize family and social networks, adapt fishing techniques, strengthen capacity and knowledge, and improve market access and supply chains. This, in turn, will ensure more sustainable fisheries and stronger, more resilient coastal communities in the long term.